Psychological management of stroke - Lincoln, Nadina B.; Wiley InterScience (Online service) (Malden, MA : John Wiley & Sons, 2012)
Psychological Management of Stroke presents a review and synthesis of the current theory and data relating to the assessment, treatment, and psychological aspects of stroke.-Provides comprehensive reviews of evidence based practice relating to stroke -Written by clinical psychologists working in stroke services -Covers a broad range of psychological aspects, including fitness to drive, decision making, prevention of stroke, and involvement of carers and families -Reviews and synthesizes new data across a wide range of areas relevant to stroke and the assessment, treatment, and care of stroke survivors and their families -Represents a novel approach to the application of psychological theory and principles in the stroke field.
Front Matter -- Section 1: Background to Stroke and Stroke Services. Experiences and Effects of Stroke and its Aftermath -- Clinical Stroke Services -- Neurological Basis of Stroke and Related Vascular Disorders -- Section 2: Cognitive Effects of Stroke. Neuropsychological Symptoms of Stroke -- Screening for Cognitive Problems after Stroke -- Neuropsychological Assessment after Stroke -- Communication Problems after Stroke -- Driving after Stroke -- Decision Making and Mental Capacity -- Neuropsychological Aspects of Rehabilitation -- Cognitive Rehabilitation -- Challenging Behaviour after Stroke -- Section 3: Emotional Effects of Stroke. Emotional Problems after Stroke -- Screening and Evaluation of Emotional Problems after Stroke -- Managing Emotional Problems after Stroke -- Behavioural and Cognitive-Behavioural Therapy for Depression after Stroke -- Stroke and Fear of Falling -- Prevention of Psychological Distress after Stroke -- Pain and Fatigue -- Section 4: Social Dimensions of Stroke. Carers of Stroke Survivors -- Strokes in Young People: Families and Children, Carers, Employment and Long-Term Survival -- Prevention of Stroke -- Conclusions and Future Directions -- Appendix 1 -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Cerebrovascular disease -- Psychological aspects; Cerebrovascular disease -- Treatment; Electronic books